HEAVY METAL CONCENTRATIONS IN SOME SELECTED VEGETABLES FROM THE VICINITY OF KAOLIN MILLING PLANT IN ALKALERI, BAUCHI STATENIGERIA - A.O. ABDULLAHI; A.B.MOHAMMED; M.J. YELWA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2017)
Heavy metals in tomato and okro vegetables from the vicinity of kaolin milling plant in Alkaleri, Bauchi state were determined. Simple random sampling method was used in sample collection. Sample collection was done three times in interval of one month. Samples were then air dried and digested using hot HCl, H2SO4 and HNO3 in the ration of 1:5:1. Elemental analysis was carried out using Atomic Absorption Spectrophotometry. The result of this study showed that the average concentration of zinc detected ranged from 9.33 to 13.20ppm in Tomato and 2.76 to 5.30ppm in Okro while cadmium varied from 1.11 to 3.17ppm and 0.59 to 1.58 in tomato and okro respectively. Chromium ranged from 0.96 to 1.48ppm (Tomato) and 1.42 to 1.98ppm (Okro), Lead detected ranged from 0.91 to 2.21ppm (Tomato) and 1.24 to 1.85ppm (Okro), Iron ranged from 33.61 to 40.0ppm(Tomato) and 12.71 to 14.99ppm (Okro) and Cobalt ranged between 3.06 to 6.46ppm (Tomato) and 1.55 to 4.42ppm (Okro). The result showed that the concentration of heavy metals varied in order of Fe> Zn> Co> Cd > Pb > Cr. All but the level of Zn and Fe were above the safe limits established by FAO and WHO.